Effects of L-alanyl-glutamine upon the blood and kidney biochemical parameters in the rat hind limb model of ischemia/reperfusion - Alves,Marcos Antonio (2005)
PURPOSE: To investigate the effects of l-alanyl-glutamine (Ala-Gln) intragastric administration upon blood and kidney metabolic parameters alterations in rats subjected to ischemia/reperfusion of hind limb. METHODS: Forty-eight male rats were randomized in 2 groups offered via gavage either saline 2.0 mL (G-1) or Ala-Gln solution 0.75 mgKg-1(G-2) once a day at 7 AM during 7 days. One-hour after the last gavage (Day 7) all rats were submitted to ether anesthesia, laparotomy and clamping of the left iliac artery for 3 h. Kidney and blood samples were collected at the end of ischemic period (3h) and at 1-3-6h during reperfusion period for metabolites (pyruvate, lactate, glucose and ketone bodies) enzymatic analysis. ATP was also assayed in kidney samples. RESULTS: Lactacemia and ketonemia were significantly increased in Ala-Gln treated rats during reperfusion. Kidney pyruvate concentrations were significantly decreased and tissue lactate concentrations were significantly increased during reperfusion (1h and 3h) in G-2 rats compared with respective controls. Glucose, ATP and ketone bodies concentrations were significantly increased in the kidney in L-Ala-Gln treated rats at 3 hours after reperfusion as compared to respective controls. CONCLUSIONS: Unilateral hind limb ischemia in L-Ala-Gln pre-treated rats may induce increased lactacemia and increased kidney lactate concentrations, indicating increased glycolytic activity in renal medulla and in other peripheral tissues. Higher ketonemia during reperfusion may reflect a possible increase in ketogenesis due to lower insulin plasma concentration hepatic signaling as a result of increased glucose oxidation in peripheral tissues, caused by the intra-gastric administration of glutamine dipeptide, suggesting also decreased insulin resistance.